1974
DOI: 10.1113/jphysiol.1974.sp010578
|View full text |Cite
|
Sign up to set email alerts
|

The distribution in the rabbit of choline administered by injection or infusion

Abstract: SUMMARY1. The concentration of choline in plasma, erythrocytes, skeletal muscle, heart, lung, liver, small intestine and kidneys and the changes that follow the injection or infusion of choline have been measured in rabbits anaesthetized with pentobarbitone.2. The concentration of choline in the plasma of arterial blood was 11-8 + 0*6 n-mole/ml. and in the erythrocytes 28*4 + 1-3 n-mole/ml. blood.3. All tissues contained a higher concentration of free choline than did plasma. The values range from 19 1 + 2-2 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

1976
1976
2010
2010

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 16 publications
2
21
0
Order By: Relevance
“…The choline concentration of the brain, intestine, skeletal muscle or heart was not appreciably (Gardiner & Gwee, 1974) Ansell & Spanner, 1971). The rise in the choline concentration of the liver caused by TPHC-3 is puzzling.…”
Section: Effect Of Hemicholinium-3 On Continuous Infusions Of Cholinementioning
confidence: 98%
See 4 more Smart Citations
“…The choline concentration of the brain, intestine, skeletal muscle or heart was not appreciably (Gardiner & Gwee, 1974) Ansell & Spanner, 1971). The rise in the choline concentration of the liver caused by TPHC-3 is puzzling.…”
Section: Effect Of Hemicholinium-3 On Continuous Infusions Of Cholinementioning
confidence: 98%
“…The concentrations of choline in muscle, heart, brain and the terminal portion of the small intestine were unaffected by the administration of either hemicholinium. The choline concentrations in the control rabbits were reported previously (Gardiner & Gwee, 1974 Gardiner (1975) further showed that the rises following (+)-tubocurarine of TPHC-3 were prevented if the animals were artificially resuscitated.…”
Section: Effect Of Hemicholinium-3 On Continuous Infusions Of Cholinementioning
confidence: 98%
See 3 more Smart Citations